Effect of oxidative modification on structural and foaming properties of egg white protein. (February 2018) - Duan, Xiang; Li, Mei; Shao, Jing; Chen, Haiying; Xu, Xueming; Jin, Zhengyu; Liu, Xuebo
Abstract: Protein oxidation results in structural modification which affects its functionalities. In this study, 2, 2′-azobis (2-amidinopropane) dihydrochloride (AAPH) was selected as a representative of lipid peroxidation products to investigate the effect of oxidative modification on structural and foaming properties of egg white protein. Incubation of egg white protein with AAPH resulted in structural changes, regarding by sulfhydryl-disulfide interchange reaction and increase in dityrosine formation. Moderate oxidation led to exposure of hydrophobic groups of egg white protein, whereas, excessive oxidation induced a decrease in surface hydrophobicity. Molecular weight distribution and scanning electron microscopy showed that egg white protein underwent an aggregation after excessive oxidation. Furthermore, after treating with AAPH at 0.2 mM, the foaming ability of egg white protein increased from 85.6% to 91.4%, and the foaming stability increased from 80.6% to 85.3%. The excessive oxidation treatment (5 and 25 mmol/L AAPH) resulted in an enhanced foaming ability, while reduced its foaming stability. This study suggested that oxidation treatment has a potential to be implemented to modify foaming properties of egg white protein. Graphical abstract: Highlights: Oxidation treatment induced sulfhydryl-disulfide interchange and dityrosine formation in egg white protein. Oxidation treatment changed surface hydrophobicity and secondary structure of egg white protein. Excessive oxidation increased foaming ability of egg white protein, while decreased its foam stability.